Design strategies to address kinetics of drug binding and residence time. Issue 10 (15th May 2015) - Cusack, Kevin P.; Wang, Ying; Hoemann, Michael Z.; Marjanovic, Jasmina; Heym, Roland G.; Vasudevan, Anil
Graphical abstract: Abstract: The kinetics of drug binding and drug residence time are recognized to be important in the clinical effectiveness of drug candidates. In most cases a long residence time of the drug-target complex results in an extended duration of pharmacodynamic activity, even when systemic concentrations of drug have been notably reduced through elimination routes. Hence, if selective for target, long residence times can increase the duration of drug efficacy in vivo and can significantly diminish the potential for off-target-mediated toxicities. Furthermore, a compound with a slower dissociation rate may allow a reduced dosing schedule relative to a compound with a rapid dissociation rate. Factors contributing to long residence time that could be useful to medicinal chemists in the prospective design of compounds with long residence times will be discussed in this perspective. Particular emphasis will be on case studies highlighting how kinetics can be measured, modulated based on supporting structure kinetic relationships and whether these effects are translatable into man.